PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENGENDALIAN BIAYA DAN PENILAIAN KINERJA - Riska Marwahidah Suryani; Nadirsyah Nadirsyah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this study was to determine how the application of accountability accounting as a cost control and performance appraisal tool. This type of research is descriptive qualitative research by making Iskandar Muda Hospital as the sole object of research. The data used in this study are primary data and secondary data by conducting literature studies, interviews, observations, and documentation to obtain the necessary data. The results of this study indicate that the application of accountability accounting at Iskandar Muda Hospital has not been good because the separation of controlled cost and uncontrolled cost has not been implemented, and also the application of accountability accounting has acted as a cost control and performance appraisal tool wih the fulfillment of cost control feasibility indicators, and comparisons between realization and budget